Using adaptable SPARQL to manipulate and to retrieve domain ontologies: application to social intelligence domain. (1st January 2013) - Monfort, Valérie; Jaziri, Wassim
SPARQL ( SPARQL Protocol and RDF Query Language ) is a protocol and a request language which supports semantics of the RDF ( Resource Description Framework ) data. Based on previous research works, we noticed different lacks such as a poor flexibility when faced with functional and technical changes. According to first results, we aim to propose, depending on changing context including profile and location, suitable ontologies which can be accessed 'upon request'. However, SPARQL queries are not able to take into account the users' requirements update and their contexts changes as well. Faced to this limitation, we propose to use aspect paradigm to extend SPARQL and to promote adaptable SPARQL queries. Consequently, the ontologies of the project are invoked by adaptable SPARQL queries. We propose a genuine implementation in this paper.